Show last authors
1 {{formula}}
2 \nabla \cdot \mathbf a = G \rho
3 {{/formula}}
4
5 {{formula}}
6 \nabla \cdot \frac{\partial \mathbf a}{\partial t} = G \frac{\partial \rho}{\partial t} = 0
7 {{/formula}}
8
9 {{formula}}
10 \mathbf j = \frac{\partial \mathbf a}{\partial t}
11 {{/formula}}
12
13 {{formula}}
14 \nabla \cdot \mathbf j = G \rho_j
15 {{/formula}}
16
17 {{formula}}
18 \rho_j = \frac{\partial \rho}{\partial t}
19 {{/formula}}
20
21 {{formula}}
22 \nabla^2 \varphi_j = -4 \pi\,G \,\rho_j
23 {{/formula}}
24
25 {{formula}}
26 \varphi_j(\mathbf r) = -G \,\frac{Q_j}{r}
27 {{/formula}}
28
29 {{formula}}
30 \varphi_j(\mathbf r) \cdot\,r= -G \,Q_j = const = \left [\frac{m^3}{s^3}\right ] \sim \mathbf v^3
31 {{/formula}}
32
33 {{formula}}
34 \varphi_s (\mathbf r) = -G \,\frac{Q_s}{r} = \left [\frac{m^2}{s^4}\right ] \sim \mathbf a^2
35 {{/formula}}
36